The selective adsorption performance and mechanism of multiwall magnetic carbon nanotubes for heavy metals in wastewater - Zhongbing Wang (Nature Portfolio, 2021)
Abstract The safe treatment of heavy metals in wastewater is directly related to human health and social development. In this paper, a new type of recyclable adsorbent is synthesized through the oxidation of enhancer and modification with magnetic nanoparticles. The new adsorbent not only inherits the advantages of multiwall carbon nanotubes (6O-MWCNTs), but also exhibits a new magnetic property and further improved adsorption capacity, which is conducive to the magnetic separation and recovery of heavy metals. The adsorption results indicate that multiwall magnetic carbon nanotubes (6O-MWCNTs@Fe3O4) have a good performance for Pb(II) selective adsorption, with a maximum adsorption capacity of 215.05 mg/g, much higher than the existing adsorption capacity of the same type of adsorbents. Under the action of an external magnetic field, 6O-MWCNTs@Fe3O4 that adsorbed metal ions can quickly achieve good separation from the solution. The joint characterization results of FTIR and XPS show that under the action of both coordination and electrostatic attraction, the C=O bond in the –COOH group is induced to open by the metal ions and transforms into an ionic bond, and the metal ions are stably adsorbed on the surface of 6O-MWCNTs@Fe3O4. Pb(II) has a stronger attraction than Cu(II) and Cd(II) to the lone pair of electrons in oxygen atoms to form complexes, due to the covalent index of Pb (6.41) is more larger than that of Cu (2.98) and Cd (2.71).These data provide a new type of recyclable adsorbent for the efficient treatment of heavy metal ions in wastewater and enrich relevant theoretical knowledge.